A New Windings Design of 24 Slot Capacitor-Start Capacitor-Run Induction Motor - Zuriman Anthony; Erhaneli Erhaneli (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The conventional method of a single phase induction motor windings design usually constructed the main and auxiliary windings in both slot. So, there was a complicated winding design if that compare to the three-phase induction motor. Because of that, this study was aimed to design a new windings design of a single phase induction motor that construction like a three-phase induction motor. This study was focused to design a 24 slot capacitor-start capacitor-run induction motor. The windings in the motor are divided in 3 group like a three-phase induction motor. The two windings act as a main windings and the other winding act as auxiliary winding. The current rating of the winding of the proposed single-phase induction motor was 2.74A. The performances of the proposed method were compared with the performances of a three-phase induction motor that had the same current rating. The motor used as a comparator was a three-phase induction of 380/220V, 2.74/4.7A, Y/Δ, cage rotor, 4 poles, 1.5 HP, 1400 RPM, 50Hz. The result of this study showed that the proposed design of single phase induction motor could be operated with better performances than the three-phase comparator induction motor’s.